A Comparative Analysis of the Water Retention Properties of Hydrogels Prepared from Melon and Orange Peels in Soils - Shiwei Fang; Yuan Zhong; Jun Wu; Yufan Xie; Liqun Cai; Minjun Li; Jun Cao; Hejie Zhao; Bo Dong (Gels)
The objective of this study was to conduct a comparative analysis of the performance of hydrogels prepared from two distinct raw materials and to identify the hydrogels with the optimal overall capacity for dry farming applications. Ten grafted polymer hydrogels were prepared from melon peel (MP) and orange peel (OP). A comparative analysis of the degree of swelling, water absorption time, pH range, reusability, and soil water retention and water-holding capacity of the two hydrogels revealed that the MP-based hydrogels exhibited superior performance in all evaluated parameters when compared to their OP-based counterparts. The treatment group of hydrogels prepared from MPs exhibited the highest degree of swelling, with an absorptive capacity of up to 765.6 g/g in ultrapure water. The optimum absorption ratio at pH = 8.1 was 606.8 g/g, as determined by Gaussian distribution modeling. The treatment group with the best reusability demonstrated an average absorption ratio of 445.0 g/g. The degree of swelling was 84.0 g/g when the process was repeated seven times. After the MP-gels were applied to the soil, it was observed that the gels enhanced the water retention and holding capacity of the sandy soil. The water retention ratio of the sandy soil was increased by 271.0% by the addition of MP-gel, and the growth of wheat was found to be normal when 1.5% to 2.0% of MP-gel was added under drought-stress conditions. In light of the necessity to reuse agricultural waste, the preparation of MP-gel can facilitate the improvement of dry farming and address the issue of water scarcity in agriculture. This offers a viable solution for the growth and management of crops under conditions of drought stress.